2015
DOI: 10.1111/ejn.13075
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms regulating spill‐over of synaptic glutamate to extrasynaptic NMDA receptors in mouse substantia nigra dopaminergic neurons

Abstract: N-Methyl-D-aspartate glutamate receptors (NMDARs) contribute to neural development, plasticity and survival, but they are also linked with neurodegeneration. NMDARs at synapses are activated by coincident glutamate release and depolarization. NMDARs distal to synapses can sometimes be recruited by 'spill-over' of glutamate during high-frequency synaptic stimulation or when glutamate uptake is compromised, and this influences the shape of NMDAR-mediated postsynaptic responses. In substantia nigra dopamine neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 60 publications
(92 reference statements)
0
33
0
Order By: Relevance
“…1B2 ). With such an arrangement, glutamate transients sufficient to activate glutamate receptors may require the accumulation of glutamate generated across multiple spikes (Asztely et al, 1997; Carter and Regehr, 2000; Clark and Cull-Candy, 2002; Chalifoux and Carter, 2011; Coddington et al, 2013; Nahir and Jahr, 2013; Wild et al, 2015). We sought to test one prediction of the distant-receptor model, which is that pharmacological blockade of glutamate transporters aligning the extrasynaptic space should enhance extrasynaptic currents induced by spike bursts (Asztely et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B2 ). With such an arrangement, glutamate transients sufficient to activate glutamate receptors may require the accumulation of glutamate generated across multiple spikes (Asztely et al, 1997; Carter and Regehr, 2000; Clark and Cull-Candy, 2002; Chalifoux and Carter, 2011; Coddington et al, 2013; Nahir and Jahr, 2013; Wild et al, 2015). We sought to test one prediction of the distant-receptor model, which is that pharmacological blockade of glutamate transporters aligning the extrasynaptic space should enhance extrasynaptic currents induced by spike bursts (Asztely et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…As a means of signaling between neurons, glutamatergic activation of extrasynaptic AMPA and NMDA receptors has been reported in a wide range of circuits (Asztely et al, 1997; Isaacson, 1999; Carter and Regher, 2000; DiGregorio et al, 2002; DeVries et al, 2006; Szapiro and Barbour, 2007; Chalifoux and Carter, 2011; Coddington et al, 2013; Wild et al, 2015). The extrasynaptic, spillover-mediated transmission that we have described between eTCs and MCs however stands out, first, because it is the primary mode of signaling between eTCs and MCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar adaptation in the VTA could greatly impact signalling onto DA neurons. In support of this hypothesis, pharmacological blockade of GLT-1 and GLAST increases activation of extrasynaptic NMDARs in DA neurons (Wild et al, 2015), and disrupting the orthologue of GLT-1 (glt-1-6) in C. elegans produces DA neuron hyperexcitability (Hardaway et al, 2015). It is conceivable, then, that certain stimulus-triggered adaptations within the VTA may be resulting from, or at least enhanced by, a reduction in astrocyte uptake of glutamate.…”
Section: Glutamate Uptakementioning
confidence: 97%
“…In addition to modulating the time course of synaptic glutamate receptor activation, astrocyte ensheathment of synapses, or lack thereof, can determine the degree to which glutamate spillover from synapses can activate pre-and extrasynaptic glutamate receptors (Oliet et al, 2001;Oliet & Bonfardin, 2010;Wild et al, 2015). This aspect of astrocyte biology merits greater scrutiny within the VTA, as studies in other regions have shown that both the structure of astrocyte processes and the level of glutamate transporters present on these processes are altered by stimuli that impact signalling in the VTA.…”
Section: Glutamate Uptakementioning
confidence: 99%